PEMANFAATAN FILTRASI MULTIMEDIA DALAM MENGOLAH AIR PAYAU DI DESA GOSONG TELAGA BARAT KABUPATEN ACEH SINGKIL - Shelvya Mulya Ivana; Mulyadi Abdul Wahid (Program Studi Teknik Lingkungan Fakultas Sains dan Teknologi UIN Ar-Raniry Banda Aceh, 2021)
Water is a basic human need. The use of water is very complex, among others, for drinking, cooking, bathing, washing, agriculture, fisheries, and so on. Coastal areas are often faced with the problem of limited water resources. In terms of quantity, coastal areas generally have abundant water, but it is often difficult to obtain water for various uses, due to inadequate quality. Limited water resources in coastal areas are related to the scarcity of fresh water that can be used as clean water. This study aims to desalinate brackish water into fresh water that can be used as clean water for sanitation hygiene needs. The process of desalinating brackish water into clean water uses the multimedia filtration method. Filtration is a process of separating solids from fluids (liquids or gases) that carry them using a porous medium or other porous material to remove as much of the suspended and colloidal fine solids as possible. The filtration media used in this study were activated carbon, silica sand, zeolite and gravel. These media are effective in reducing salinity and turbidity in brackish water.